The Effect of Special Exercises in some Biochemical Variables and the Technical Performance of the Front Bow Skill on the Mat of Ground Movements in the Artistic Gymnastics for Women - Mizher, Noor Rahman (International Journal of Psychosocial Rehabilitation, 2020)
The development in the sport of gymnastics is the result of the progress made on the technical and research levels that helped athletes in performing difficult and complex skills through which they won many Olympic decorations, and since most of the skills of gymnastics require a complex motor structure, and bow skill is an important skill in gymnastics, so therefore Trainers and teachers are required to formulate and develop comprehensive educational and training curricula to develop most of these skills. Through the researchers ’follow- up to the lessons of the technical gymnastics, as a teacher of the gymnastic subject, they noticed a problem that lies in the poor performance of female students in the front arc skill on the floor of the movements of the floor. The performance. The research objective to: • Developing special exercises to improve some biochemical variables and the technical performance of the front bow skill on the floor of the students’ ground movements. • Knowing the effect of special exercises on some biochemical variables and the technical performance of the front bow skill on the mat of the ground movements of the students. The research community has identified the third stage students, Department of Physical Education and Sports Science, College of Education for Girls, University of Kufa for the academic year (2018-2019), and the number is (25) students. Accordingly, the research sample was chosen from that community by (20) students. • There is a positive effect of special exercises and stomach on scientific basis in the development of some biochemical variables of the skill of the front arc on the ground of the movements of the ground. • The special exercises proved their effectiveness in developing biochemical variables in all stages of the skill (preparatory, main, and final). The technical performance of the front arc skill on the ground of the ground